A new psychotherapy for traditional men - Brooks, Gary R. (Jossey Bass Publishers, 1998)
Psychologist Gary Brooks has developed an innovative (and user-friendly) therapeutic model for working with men who are resistant to traditional therapy. Drawing on his own blue-collar upbringing and his work in veterans hospitals treating working-class clients, Brooks shows how this unique approach uses compassion, respect, empathy, and sensitivity to dissolve the barriers of men's defenses.